2019
DOI: 10.2196/12148
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Orthopedic Surgeons on the Clinical Use of Bioprinted Cartilage: Qualitative Study

Abstract: Background: Over the past 60 years, no technique used for treating cartilage disorders has been completely successful. Bioprinting provides a highly anticipated, novel alternative solution to this problem. However, identifying barriers to this new technology is crucial in order to overcome them when bioprinting reaches the implementation stage. This kind of research has been declared essential because clinical efficacy and safety studies alone do not always lead to successful implementation.Objective: This qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In our previous research [24], which identified the barriers and facilitators for the bioprinted cartilage use and this new approach, we validated the conclusion that orthopedic surgeons should receive information of higher quality from reliable sources, thus enabling the implementation of the bioprinted cartilage, and that researchers should consider what surgeons believe the cartilage graft should be like.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In our previous research [24], which identified the barriers and facilitators for the bioprinted cartilage use and this new approach, we validated the conclusion that orthopedic surgeons should receive information of higher quality from reliable sources, thus enabling the implementation of the bioprinted cartilage, and that researchers should consider what surgeons believe the cartilage graft should be like.…”
Section: Discussionsupporting
confidence: 57%
“…The results of this study show that the information received impacts the decision-making process of orthopedic surgeons in a complex and diverse way, as it depends on several variables: the type and origin of the information and its relevance to their demographic data. Previous research [24] found that the amount and quality of the information received was one of the main barriers for the implementation of new technologies. The sample analyzed here shows that orthopedic surgeons lack the specific knowledge of 3D printing as applied to cartilage (Table 4), where 50% of the survey participants who admit to being informed in an unspecific way have almost zero knowledge about it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Better understanding of how to optimize patient care can improve outcomes and quality of life, allowing more efficient use of health resources. Results of previous research [7,8] suggest that the most logical next step is to examine surgeons’ responses to this new therapeutic possibility. Reviewing, analyzing, and categorizing the different research activities in this new field [9] will help define the scope and depth of future research and identify gaps in critical knowledge [10].…”
Section: Introductionmentioning
confidence: 99%